CHORAL READING AND SQ3R METHODS IN TEACHING READING AT THE SEVENTH GRADE STUDENTS AT MTSN 1 PONOROGO - Untari, Sri; Sri Agung, Winantu Kurnianingtyas (Journal of Language, Literature and Teaching, 2023)
AbstractReading is one of several skills that students must master in learning English. Teacher needs proper methods especially in teaching reading. Implementing the teaching method affects student learning outcomes, so the teacher should consider the appropriate teaching methods by initiating the class environment and the student's condition.The aims of this research are; 1. To identify how the implementation of choral reading and SQ3R methods are used by the teacher, 2. What the problems are found by the teacher in applying these methods, and 3. What the teacher’s ways are to overcome the problems in applying these methods in teaching reading at the seventh-grade students at MTsN 1 Ponorogo.This research was conducted at MTsN 1 Ponorogo by using descriptive qualitative method. The data was collected through observation, interview, and documentation. The data from interview and observation were obtained in the form of interview and observation transcripts, and the documentation results were in the form of lesson plan. The data were analyzed using the theory of Miles and Huberman. The steps were data reduction, data display, and drawing conclusion. To test the validity of the data, the researcher used triangulation of data sources.The researcher found that the implementation of Choral Reading and SQ3R methods was divided into some steps. The steps of the choral reading method were the teacher gave an example of the correct reading, the students were repeated after the teacher, and the teacher went around to check the students' mistakes. The steps in the SQ3R method were survey, read, recite, and review. The problems faced by the teacher in applying these methods were students were not enthusiastic about following the lesson, and students often did not bring dictionaries. Meanwhile, the problems were solved by announcing that the students must submit an assignment, and the teacher consistently used the methods over several meetings and instructed the students to borrow a dictionary from a friend in another class or at the library.Keywords: Teaching Method, Teaching Reading, Choral Reading, SQ3R